Efektifitas Kebijaksanaan Pemerintah, Sumber Daya dan Budaya Ekonomi Terhadap Peningkatan Pemberdayaan Ekonomi Masyarakat di Provinsi Kalimantan Timur - Lca. Robin Jonathan (Prodi Ilmu Administrasi Negara, 2016)
This study was conducted to determine the effect of the effectiveness of government policy, resources and culture of the local economy to increase economic empowerment of society. The effectiveness of government policy (X1), resources (X2) and culture of the local economy (X3) as the independent variable and the economic empowerment as the dependent variable. This research is located in the city of Samarinda, East Kalimantan. Samples were taken at random as many as 100 families were considered to be representative of the population with the data collection instrument used was a questionnaire. Data analysis technique used is multiple linear regression analysis, using SPSS version 16.0.1. From the data analysis it is concluded that the effectiveness of government policy, resource, economic cultural society has positive and significant impact on the improvement of economic empowerment in Samarinda, East Kalimantan province with multiple linear regression equation Y = 0.636 + 0,040X1 + 0,042X2 + 0,753X3. Whereas the value of R² (coefficient determination) of 0.653, which means that all independent variables affect the dependent variable changes in value amounted to 65.30%.